2015
DOI: 10.1161/strokeaha.114.007649
|View full text |Cite
|
Sign up to set email alerts
|

Genes From a Translational Analysis Support a Multifactorial Nature of White Matter Hyperintensities

Abstract: Supplemental Digital Content is available in the text.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
26
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(29 citation statements)
references
References 43 publications
1
26
0
2
Order By: Relevance
“…Differential gene effects can be observed in humans with WM hyperintensities (WMH). 25 An magnetic resonance imaging study in patients with SVD showed not only that hypertension could be a predictor of WMH damage in patients with mild stroke but also that salt intake itself is associated with WMH, independent of hypertension. 15 It is well known that there are salt-resistant and salt-sensitive hypertensive patients, the latter of whom has been associated with greater endothelial dysfunction, characterized by defective endothelium-dependent…”
Section: Pathological Cascade Of Svd: Roles Of Hypertension and Saltmentioning
confidence: 99%
See 3 more Smart Citations
“…Differential gene effects can be observed in humans with WM hyperintensities (WMH). 25 An magnetic resonance imaging study in patients with SVD showed not only that hypertension could be a predictor of WMH damage in patients with mild stroke but also that salt intake itself is associated with WMH, independent of hypertension. 15 It is well known that there are salt-resistant and salt-sensitive hypertensive patients, the latter of whom has been associated with greater endothelial dysfunction, characterized by defective endothelium-dependent…”
Section: Pathological Cascade Of Svd: Roles Of Hypertension and Saltmentioning
confidence: 99%
“…Genes differently expressed in brains of SHRSPs of 5, 16, and 21 weeks of age, compared with controls, include those related to glial activity (increased), endothelial tight junctions (reduced), and vascular reactivity (impaired), 23 some of which have also been identified in human gene analysis of WMH. 25 It has been increasingly recognized that oligodendrocyte precursor cells themselves also play a pivotal role in promoting BBB integrity by the secretion of transforming growth factor-β1. 93 Moreover, electron microscopy has demonstrated that oligodendrocyte precursor cells and pericytes directly adhere to and communicate with each other via basal lamina to promote their proliferation and differentiation.…”
Section: Important Roles Of Cell Components Of Bbb In Svdmentioning
confidence: 99%
See 2 more Smart Citations
“…Evidence is also accumulating that mutation of mitochondrial ribosomal protein genes is involved in impaired mitochondrial translation leading to neurological diseases (Boczonadi and Horvath, 2014). Of note, MRPL18, another mitochondrial ribosomal protein gene that was found to be upregulated in active multiple sclerosis lesions (Fischer et al, 2012), was also differentially expressed in brains of young spontaneously hypertensive stroke-prone rats and associated with WMH (Lopez et al, 2015). Taken together, these data provide biological plausibility supporting the role of MRPL38 dysfunction in the pathophysiologic changes in the nervous sys- Fig.…”
Section: Discussionmentioning
confidence: 99%